La représentation de la vie d’un maître estropié du passé au xixe siècle : L’Aleijadinho d’Henrique Bernardelli - Fábio D’Almeida (Les Cahiers de l'École du Louvre)
This article proposes to analyse the painting Aleijadinho, le sculpteur Antonio Francisco Lisboa by the Brazilian painter Henrique Bernardelli, the first and only representation known from the lifetime of a master of the Latin American colonial past in the nineteenth century. We will attempt to place this work in the Brazilian artistic context, notably that of the representation of the artists of the past and present. We will discuss how Bernardelli’s painting is inspired by in a very particular way by the first biography dedicated to the sculptor, in the 1850s, to set up the idea of a predestined genius of the Brazilian colonial past. The analysis of the painting will highlight the way in which the canvas distances itself considerably from the formulas that are frequently present in the European book also figuring the lives of the Old Masters in the nineteenth century.Antonio Francisco Lisboa, Aleijadinho, peinture brésilienne, xixe siècle, maîtres anciens, art colonial, genre anecdotique, histoire des artistes